Discovery Learning using Multiple Representation model for enhancing scientific processing and critical thinking skills of the students - Syahmel Syahmel; Jumadi Jumadi (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2019)
This study aims to reveal: (1) the feasibility of the developed Discovery Learning using Multiple Representations (DLMRs) model on the subject matter “Substance Pressure and its Application in Daily Life” for grade 8 students of SMP, (2) the practicality of the developed DLMRs model for science teachers and grade 8 students of SMP, and (3) the effectiveness of the developed DLMRs model in improving the science process and critical thinking skills of grade 8 students of SMP. This research is research and development adapting the development procedures by Borg Gall which consisted of 10 steps: (1) research and information collection, (2) planning, (3) developing the preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision, and (10) dissemination and implementation. The limited trial subjects consist of 15 students of class VIII.4 SMPN 1 Watopute. The subjects of the field trial in the experimental class consist of 31 students of class VIII.1 and those in the control class consist of 32 students of class VIII.3 SMPN 1 Watopute. The used sampling technique is cluster sampling. The instrument of data collection is an essay test to measure critical thinking skills, observation sheets to measure science process skills, questionnaires to determine the readability of the DLMRs student worksheet, and questionnaires to determine student and teacher responses to DLMRs model. The data analysis technique used is the MANOVA test with a significance level of 0.05. The results showed that: (1) the developed DLMRs model was feasible to implement based on experts judgment, (2) the DLMRs model is practical for teaching science based on responses given by teachers and students, (3) the DLMRs model is effective for improving students' science process skills, (4) the DLMRs model is effective for enhancing students' critical thinking skills.